PENGARUH KEPEMIMPINAN, LINGKUNGAN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI PEMERINTAH KANTOR KECAMATAN DUREN SAWIT JAKARTA TIMUR - Mario (ITB AAS Indonesia Surakarta, 2025)
Human Resource Management (HRM) at the sub-district level is an effort to manage the apparatus responsible for carrying out government duties within the sub-district. This study aimed to examine and analyze the influence of leadership, work environment, and work motivation on employee performance in Duren Sawit Sub-district, East Jakarta. This research falls into the explanatory research category, aiming to explain the causal relationship between the variables under study. Data collection was conducted through the distribution of questionnaires to predetermined respondents. To test the proposed hypothesis, multiple linear regression analysis was used because it is considered appropriate for analyzing the influence of more than one independent variable on the dependent variable. The sample selection was carried out using the accidental sampling method, which is a sampling technique based on anyone the researcher encounters by chance and is considered relevant as a data source. The number of samples collected in this study was 220 respondents. The results of the coefficient of determination test show that 26.9% of employee performance variations can be explained by leadership, work environment, and work motivation variables, while the remaining 73.1% is influenced by other factors outside this study. The F test shows that simultaneously the three independent variables have a positive and significant effect on employee performance, with a calculated F value of 27.876 which is greater than the F table of 3.040. Furthermore, the results of the t test show that leadership obtains a calculated t value of 5.271, work environment 5.511, and work motivation 3.558, all of which are greater than the t table of 1.132. Thus, partially leadership, work environment, and work motivation are proven to have a positive and significant effect on employee performance in Duren Sawit District, East Jakarta. Keywords: Leadership, Work environment, Work motivation, Employee Performance